Selective Induction of DNA Repair Pathways in Human B Cells Activated by CD4+ T Cells - Wu, Xiaosheng; Tschumper, Renee C.; Gutierrez, Albert, Jr.; Mihalcik, Stephen A.; Nowakowski, Grzegorz S.; Jelinek, Diane F. (PLOS ONE, 2010)
Greater than 75% of all hematologic malignancies derive from germinal center (GC) or post-GC B cells, suggesting that the GC reaction predisposes B cells to tumorigenesis. Because GC B cells acquire expression of the highly mutagenic enzyme activation-induced cytidine deaminase (AID), GC B cells may require additional DNA repair capacity. The goal of this study was to investigate whether normal human B cells acquire enhanced expression of DNA repair factors upon AID induction. We first demonstrated that several DNA mismatch repair, homologous recombination, base excision repair, and ATR signaling genes were overexpressed in GC B cells relative to naïve and memory B cells, reflecting activation of a process we have termed somatic hyperrepair (SHR). Using an in vitro system, we next characterized activation signals required to induce AID expression and SHR. Although AID expression was induced by a variety of polyclonal activators, SHR induction strictly required signals provided by contact with activated CD4+ T cells, and B cells activated in this manner displayed reduced levels of DNA damage-induced apoptosis. We further show the induction of SHR is independent of AID expression, as GC B cells from AID -/- mice retained heightened expression of SHR proteins. In consideration of the critical role that CD4+ T cells play in inducing the SHR process, our data suggest a novel role for CD4+ T cells in the tumor suppression of GC/post-GC B cells.